Penerapan Dialektika Guru dan Murid dalam Perspektif Hegel untuk Meningkatkan Proses Belajar Mengajar Siswa Kelas 2 MTs Nur Muhammad Klakah Lumajang Tahun Ajaran 2021-2022 - Muhaiminah Darajat; Hafizh Idri Purbajati (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2023)
This study discusses the application of the concept of dialectics in Hegel’s perspective to improve the teaching and learning process of grade 2 students of MTs Nur Muhammad Klakah Lumajang in the 2021-2022 academic year. The concept of Hegel’s dialectics, which consists of thesis, antithesis, and synthesis, is the basis for building dynamic interactions between teachers and students. The application of this concept is carried out through discussion methods, project-based learning, and problem-based learning to encourage critical thinking and the development of deeper understanding. This study uses a qualitative approach with a case study method to observe the effectiveness of the implementation of the dialectics concept in learning. Data were collected through direct observation in class, interviews with teachers and students, and analysis of learning documents. Data analysis techniques used include data reduction, data presentation, and drawing conclusions. The results of the study show that the application of dialectics in learning can increase student engagement, strengthen analytical thinking skills, and create a more interactive learning atmosphere. Thus, the concept of Hegel’s dialectics can be an effective strategy in improving the quality of education and forming critical and reflective student characters.